2020
DOI: 10.1002/etc.4886
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Neonicotinoid Acetamiprid in Pollen on Bombus impatiens Microcolony Development

Abstract: Honey bees and other wild bee species including bumble bees have experienced population declines in recent decades. Although many stressors are implicated in bee population declines, much attention has focused on neonicotinoid pesticides, which are widely used and known to be toxic to pollinators. One neonicotinoid, acetamiprid, has been studied very little in bumble bees, despite its use on bumble bee-pollinated crops. We assessed the impacts of acetamiprid to the North American bumble bee Bombus impatiens us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 65 publications
(74 reference statements)
2
5
0
Order By: Relevance
“…Studies have showed its relation to reduced sperm density in birds, and it is claimed that agriculture contributes to the decline in farmland bird populations (Humann-Guilleminot et al, 2019). This pesticide is also associated with detrimental impacts for pollinators and ecosystem services (Camp et al, 2020). Acetamiprid was not found in surface waters which is consistent with other studies, where it has been infrequently detected and if so, with concentrations below LOQ; similar results have been found for this compound in biota (Miller et al, 2019).…”
Section: Pesticidessupporting
confidence: 84%
“…Studies have showed its relation to reduced sperm density in birds, and it is claimed that agriculture contributes to the decline in farmland bird populations (Humann-Guilleminot et al, 2019). This pesticide is also associated with detrimental impacts for pollinators and ecosystem services (Camp et al, 2020). Acetamiprid was not found in surface waters which is consistent with other studies, where it has been infrequently detected and if so, with concentrations below LOQ; similar results have been found for this compound in biota (Miller et al, 2019).…”
Section: Pesticidessupporting
confidence: 84%
“…Specifically, acetamiprid treatments at both concentrations affected the time to the first feeding and the number of feedings at the second‐exploited patch depending on individual body mass, although this altered behaviour did not result in reduced syrup consumption during the one‐hour‐long trial. Thus, while we also confirmed that chronic exposure even to a high concentration of acetamiprid does not reduce bumblebees' survival (as in Camp, Batres, et al., 2020; Camp, Williams, et al., 2020; Reid et al., 2020; Van Oystaeyen et al., 2021), our findings indicate that exposure to this pesticide may not be without consequences in a foraging context.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies on the effects of acetamiprid primarily investigated overall syrup and pollen consumption in microcolonies (Camp, Batres, et al., 2020; Camp, Williams, et al., 2020; Chandler et al., 2020), but did not quantify how the applied treatment affected individual foraging behaviour. In other neonicotinoids, however, a wide variety of dose‐dependent behavioural effects have been described in foragers that could provide a mechanistic explanation for the reduced foraging efficiency and poor colony performance in colonies exposed to such pesticides (e.g., Feltham et al., 2014; Gill & Raine, 2014; Stanley et al., 2016; Whitehorn et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, two studies reported data on mortality associated with chronic exposure to different doses of acetamiprid in B. impatiens microcolonies. Camp et al (2020a) found that even the highest concentration of analytical acetamiprid in pollen (4520 μg/kg) did not increase worker mortality during a 6-week-long observation period, and worker behaviour was unaffected by all levels of exposure. Similarly, even the highest dose of acetamiprid in syrup (11300 μg/L) had no adverse effect on worker survival over 7 weeks (on the contrary, the highest concentration group had a significantly higher survival than the control group), while altered behaviour (i.e.…”
Section: Chronic Oral Toxicitymentioning
confidence: 87%